Dietary Proteins Relevant to Human Consumption Impact the Development of Obesity and Type 2 Diabetes in Association with Major Changes in the Gut Microbiota in a Mouse Model (OR27-03-19). (13th June 2019) - Daniel, Noëmie; Choi, Béatrice; Houde, Vanessa; Varin, Thibault; Vors, Cecile; St-Pierre, Philippe; Marette, André
Abstract: Objectives: Animal models fed a high-fat high-sucrose (HFHS) diet are commonly used to study obesity and cardiometabolic diseases. While much attention is paid to the impact of fat and carbohydrates sources, very little consideration is given to the composition of dietary proteins. Indeed, casein is often the only source of protein in rodent's diet. This study aimed to evaluate the impact of a dietary protein mix that is more relevant to typical intakes of proteins in humans and its influences on body weight gain, metabolic health and gut microbiota. Methods: Our new diet contained a mix of 10 protein sources based on NHANES data that were incorporated into low-fat low-sucrose (LFLS) and HFHS diets. C57BL/6J mice were fed these diets or control diets containing identical amounts of casein as the only source of protein for 12 weeks. Feces were collected for gut microbiota investigation, an oral glucose tolerance test was performed and tissues were harvested for analysis of insulin signaling and mTOR/S6K1 activation. Results: 16S rRNA gene sequencing of fecal samples showed that both LFLS and HFHS mice fed the protein mix had increased gut microbiota diversity, and significant changes in the relative abundance of several bacterial species (higher Adlercreutzia or Tyzzerella, lower Bacteroides or Akkermansia) as compared to mice fed casein only. Importantly, inclusion of the protein mix amplified the effects of the HFHS diet on the development of obesity, glucose intolerance and hyperinsulinemia as compared to casein-fed animals, whereas no difference was observed in the context of LFLS feeding. Evaluation of insulin signaling in the liver also revealed that the protein mix potentiated the effect of HFHS feeding on the mTORC1/S6K1 pathway, increasing inhibitory phosphorylation of IRS-1 on Ser1101 and leading to further impairment of Akt activation by insulin. Conclusions: Our results reveal that compared to pure casein, feeding a protein mixture causes major changes in the gut microbiota profile and greater impact on HFHS-induced obesity and associated metabolic impairments. This study illustrates the importance of considering a diverse source of dietary proteins when using laboratory animal models to more reliably reproduce the development of metabolic syndrome in humans, and to enhance the clinical relevance of nutritional and therapeutic interventions. Funding Sources: N/A.